VD_FINDINFO Arrêt / 2016 / 546 vom 16. Juni 2016 - VD Tribunal cantonal (2016)
AVANCE DE FRAIS, DÉCISION D'IRRECEVABILITÉ | 69 al. 1bis LAI, 61 let. a LPGA, 47 al. 2 LPA-VD, 47 al. 3 LPA-VD, 47 al. 4 LPA-VD